Remarkably Divergent Regions Punctuate the Genome Assembly of the Caenorhabditis elegans Hawaiian Strain CB4856. Issue 3 (19th May 2015) - Thompson, Owen A; Snoek, L Basten; Nijveen, Harm; Sterken, Mark G; Volkers, Rita J M; Brenchley, Rachel; van't Hof, Arjen; Bevers, Roel P J; Cossins, Andrew R; Yanai, Itai; Hajnal, Alex; Schmid, Tobias; et al.
Abstract: The Hawaiian strain (CB4856 ) of Caenorhabditis elegans is one of the most divergent from the canonical laboratory strain N2 and has been widely used in developmental, population, and evolutionary studies. To enhance the utility of the strain, we have generated a draft sequence of the CB4856 genome, exploiting a variety of resources and strategies. When compared against the N2 reference, the CB4856 genome has 327, 050 single nucleotide variants (SNVs) and 79, 529 insertion–deletion events that result in a total of 3.3 Mb of N2 sequence missing from CB4856 and 1.4 Mb of sequence present in CB4856 but not present in N2 . As previously reported, the density of SNVs varies along the chromosomes, with the arms of chromosomes showing greater average variation than the centers. In addition, we find 61 regions totaling 2.8 Mb, distributed across all six chromosomes, which have a greatly elevated SNV density, ranging from 2 to 16% SNVs. A survey of other wild isolates show that the two alternative haplotypes for each region are widely distributed, suggesting they have been maintained by balancing selection over long evolutionary times. These divergent regions contain an abundance of genes from large rapidly evolving families encoding F-box, MATH, BATH, seven-transmembrane G-coupled receptors, and nuclear hormone receptors, suggesting that they provide selective advantages in natural environments. The draft sequence makes available a comprehensive catalog of sequence differences between the CB4856 and N2 strains that will facilitate the molecular dissection of their phenotypic differences. Our work also emphasizes the importance of going beyond simple alignment of reads to a reference genome when assessing differences between genomes.